A Bugs Life: Competition Among Species Towards the Environment - Giovanni Bella (Fondazione Eni Enrico Mattei (FEEM), 2007)
A model of different species competing for the same environment is presented, and possible explanations of peaceful coexistence or rather internecine conflicts are consequently derived. By means of a Lotka-Volterra dynamic system we describe the evolution of two populations (bees and locusts) that differently approach the management of those natural resources they contend for, and thus make a simple parable of todays societies playing the current environmental scenario.
Keywords: C61; Q34; Q57; 330; Competing; Species; Lotka-Volterra; Dynamics; Natural Resource Management